Reoperation rate and indication for reoperation after free functional muscle transfers in traumatic brachial plexus injury - Pichitchai Atthakomol (2020)
© BY THE ARCHIVES OF BONE AND JOINT SURGERY. Background: Free functional gracilis muscle transfers (FFGT) are an option for reconstruction after traumatic brachial plexus injury. Few studies report the rate of revision surgeries following free functional muscle transfers. We examined the reoperation rate and indication for reoperation after primary reconstruction of upper extremity function with a free gracilis transfer after brachial plexus injury. Methods: From 2003-2016, we identified 25 patients who underwent a free functional gracilis muscle transfer for restoration of upper extremity function. We reviewed their medical charts to record patient, injury, and treatment characteristics. Indication for reoperation and reoperative procedure were also identified. Results: Fourteen out of 25 patients (56%) had a reoperation after FFGT. Four flaps were re-explored for vascular compromise, but there were no flap failures. The majority of reoperations involved adjustment of tendon excursion (8/14) which demonstrated that tenolysis was the main procedure. Conclusion: Despite promising results of free functional gracilis transfers, reoperation is relatively common and should be discussed with the patient as a preoperative strategy. Early exploration of vascular compromise may decrease the flap failure. Poor tendon excursion is a common unpredicted consequence after FFMT and is the main indication for reoperation.